2006
DOI: 10.1016/j.yexcr.2006.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Dual treatment with COX-2 inhibitor and sodium arsenite leads to induction of surface Fas Ligand expression and Fas-Ligand-mediated apoptosis in human melanoma cells

Abstract: Most human melanomas express Fas receptor on the cell surface, and treatment with exogenous Fas Ligand (FasL) efficiently induces apoptosis of these cells. In contrast, endogenous surface expression of FasL is suppressed in Fas-positive melanomas. We report here the use of a combination of sodium arsenite, an inhibitor of NF-κB activation, and NS398, a cyclooxygenase-2 (COX-2) inhibitor, for restoration of the surface FasL expression. We observed a large increase of Fas-mediated apoptosis in Fas-positive melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 85 publications
0
17
2
Order By: Relevance
“…7A and B), indicating a possible role of COX-2 in the regulation of TRAIL protein translocation to the cell surface. Unexpectedly, the effect of COX-2 suppression combined with arsenite on TRAIL surface expression was the reverse to the previously observed upregulation of FasL surface expression in these conditions [48]. However, arsenite-induced apoptosis of melanoma cells with suppressed COX-2 was dramatically increased.…”
Section: Cox-2 Suppression Downregulates Cflip Levels and Acceleratescontrasting
confidence: 53%
See 3 more Smart Citations
“…7A and B), indicating a possible role of COX-2 in the regulation of TRAIL protein translocation to the cell surface. Unexpectedly, the effect of COX-2 suppression combined with arsenite on TRAIL surface expression was the reverse to the previously observed upregulation of FasL surface expression in these conditions [48]. However, arsenite-induced apoptosis of melanoma cells with suppressed COX-2 was dramatically increased.…”
Section: Cox-2 Suppression Downregulates Cflip Levels and Acceleratescontrasting
confidence: 53%
“…However, the COX-2--prostaglandin E2 pathway possess multiple targets in the cell, in addition to regulation of cFLIP expression. COX-2 suppression dramatically increased sensitivity to sodium arsenite treatment in human melanomas, due to both cFLIP downregulation and upregulation of surface expression FasL [48], increasing levels of FasLmediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have demonstrated that arsenite has in vitro activity against melanoma as a single agent (Ivanov et al, 2004) or in combination with inhibitors of Epidermal Growth Factor Receptor (EGFR) (Ivanov et al, 2005) or cyclooxygenase 2 (COX-2) (Ivanov et al, 2006). The current study not only confirms that arsenite alone or in combination with inhibitors of arsenite detoxification is effective at killing melanoma cells, but also indicates that the broad variance in sensitivity to pharmacological concentrations of arsenic across different cell types may not be a consequence of reduced intracellular drug accumulation but rather due to mitotic spindle checkpoint dysfunction.…”
Section: As Well As In Non-apl Cell Lines (Bachleitner-hofmann Et Almentioning
confidence: 99%